2015
DOI: 10.1074/jbc.m114.621698
|View full text |Cite
|
Sign up to set email alerts
|

Peptidylprolyl Isomerase Pin1 Directly Enhances the DNA Binding Functions of Estrogen Receptor α

Abstract: Background: Estrogen receptor ␣ (ER␣) activity in breast cancer cells is increased by Pin1, an isomerase that alters protein conformation. Results: Pin1-mediated isomerization increases ER␣ DNA binding affinity. Conclusion: Pin1 allosterically regulates ER␣ DNA binding directly via isomerization of phosphorylated receptor. Significance: Pin1 regulation of ER␣ provides a framework for understanding regulation by intrinsically disordered domains on transcription factor function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 87 publications
2
19
0
Order By: Relevance
“…Pin1 has been reported to directly enhance the DNA binding functions of oestrogen receptor α (ERα). Pin1 selectively enhances the binding affinity of ER to consensus DNA elements that Pin1 isomerization of phosphorylated ERα directly regulates the function of the adjacent DNA binding domain, and this interaction is further modulated by ligand binding in the ligand‐binding domain 39 . Our study identified two binding sites of Pin1 and p65 in the IL‐18 promoter and confirmed that the two molecules simultaneously bind to the promoter region and enhance transcription.…”
Section: Discussionsupporting
confidence: 69%
“…Pin1 has been reported to directly enhance the DNA binding functions of oestrogen receptor α (ERα). Pin1 selectively enhances the binding affinity of ER to consensus DNA elements that Pin1 isomerization of phosphorylated ERα directly regulates the function of the adjacent DNA binding domain, and this interaction is further modulated by ligand binding in the ligand‐binding domain 39 . Our study identified two binding sites of Pin1 and p65 in the IL‐18 promoter and confirmed that the two molecules simultaneously bind to the promoter region and enhance transcription.…”
Section: Discussionsupporting
confidence: 69%
“…Pin1 binds to the N-terminal Ser118-Pro motif in the intrinsic activation function 1 (AF1) domain of ERα (Rajbhandari et al, 2012). Binding of Pin1 and the subsequent Pin1-mediated conformational change via isomerization increases ERα DNA binding activity with a concomitant increase in ERα transcriptional activity in estrogen activated breast cancer cells (Rajbhandari et al, 2015). Pin1 also promotes the binding of c-Myc to the DNA, independent of the protein stability regulated by Pin1 (Farrell et al, 2013).…”
Section: Dna Binding and Transactivationmentioning
confidence: 99%
“…This regulation requires Pin1 PPIase activity and the phosphorylation of c-Myc on Ser62-Pro63. While Pin1 stimulates the DNA binding activity of ERa and c-Myc, but the Pin1 binding motifs on ERa or c-Myc are not within the DNA binding domain (Farrell et al, 2013;Rajbhandari et al, 2015). How Pin1-mediated isomerization in one region could affect the activity of the DNA binding domain on a different region?…”
Section: Dna Binding and Transactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Once activated by chemicals, including a wide spectrum of endocrine disrupting chemicals, ER can further bind specific DNA sequences as a homodimer and modulate the expression of genes. [6][7][8][9] The ligand-depend mechanism of ER is depended on its structures. In common with all members of the nuclear receptor family, ER is a multi-domain protein composed of a shared architecture.…”
Section: Introductionmentioning
confidence: 99%